A review of the applications of different drying methods of banana flour preparation - Umairah Balqis Adawiyah, Z; *Hasmadi, M. (Rynnye Lyan Resources, 2023)
The perishable nature of bananas, which is highly susceptible to physical, mechanical, and physiological damage, could result in significant postharvest loss and waste. Drying is extensively used to preserve the storage life of agricultural products, thereby allowing their whole-year availability. It also assists in the development of value-added products, such as banana flour. However, despite its ability to preserve fresh materials, drying can also alter the chemical, nutritional, and functional properties of the resultant products. Hence, the selection of the most suitable method and operating parameters is critical to minimize alterations in product quality during drying. This article aimed to review and compare various drying methods applied in previous research on banana flour preparation. In general, sun-, solar-, and oven-dried banana flour often present low quality, whereas freeze-dried banana flour presents good quality. However, the results vary according to the operating parameters employed in each study.